ركن الخطأ في المسؤولية التقصيرية في التشريع الجزائري - صوراية عيساوي (My University, 2025)
Abstract : Tort liability is a fundamental cornerstone of civil law, aiming to compensate for damages resulting from the acts of fault was the sole essential component for its establishment.however, the concept of fault has undergone a notable evolution in legal and jurisprudential thought,influenced by social,economic,and technological changes,and by the continuous pursuit of greater justice and better protection for victims.This evolution is manifested in the progression from a strict requirement for proving fault to an easing of its proof, then to its simple (rebuttable) presumption,and ultimately to its irrebuttable (conclusive) presumption.The evolution did not stop there but extended to include models of objective (or strict) liability,which focus on the harm and the activity causing it.This trajectory culminated in the adoption of the precautionary principle, which mandates taking proactive measures to prevent harm, thereby making the mere endangerment of others a potential basis for liability. ........................ الملخص: تعد المسؤولية التقصيرية ركيزة أساسية في القانون المدني هدفها تعويض الأضرار الناجمة عن أفعال الغير، وقد كان ركن الخطأ على مر العصور هو العنصر الجوهري الوحيد لقيامها، غير أن مفهوم الخطأ شهد تطورا ملحوظا في الفكر القانوني والفقهي ، متأثرا بالتغيرات الاجتماعية والاقتصادية والتكنولوجية ، وبالسعي المستمر لتحقيق عدالة أكبر وحماية أفضل للمتضررين يتجلى هذا التطور في التدرج من التشدد في إثبات الخطأ إلى تخفيف عبء إثباته، ثم إلى إفتراضه إفتراضا بسيطا قابلا للدحض، وصولا إلى إفتراضه القاطع. ولم يقف التطور عند هذا الحد بل إمتد ليشمل نماذج المسؤولية الموضوعية، التي تركز على الضرر والنشاط المسبب له ، وتوج هذا المسار بتبني مبدأ الحيطة الذي يفرض إتخاذ تدابير إستباقية لمنع الضرر، جاعلا من مجرد تعريض الغير للخطر أساسا محتملا للمسؤولية . .................... Abstract : Tort liability is a fundamental cornerstone of civil law, aiming to compensate for damages resulting from the acts of fault was the sole essential component for its establishment.however, the concept of fault has undergone a notable evolution in legal and jurisprudential thought,influenced by social,economic,and technological changes,and by the continuous pursuit of greater justice and better protection for victims.This evolution is manifested in the progression from a strict requirement for proving fault to an easing of its proof, then to its simple (rebuttable) presumption,and ultimately to its irrebuttable (conclusive) presumption.The evolution did not stop there but extended to include models of objective (or strict) liability,which focus on the harm and the activity causing it.This trajectory culminated in the adoption of the precautionary principle, which mandates taking proactive measures to prevent harm, thereby making the mere endangerment of others a potential basis for liability.
Keywords: Keywords: Tort liability - Precautionary principle –fault element - Objective liability-dammage.; الكلمات المفتاحية: المسؤولية التقصيرية- الخطأ – المسؤولية الموضوعية- مبدأ الحيطة – الضرر.; Les Mots clés : La responsabilité délictuelle- La faute- Résponsabilité objective - Principe de précaution- Dommage-